IS THE WAGE RATE THE REAL ANCHOR OF THE INFLATION TARGETING MONETARY POLICY FRAMEWORK? - Perrotini Hernández, Ignacio; Vázquez Muñóz, Juan Alberto (Investigación Económica, 2018)
Numerous central banks (CBs) focus on controlling the nominal interest rate (i) to sway the price level and meet the inflation target (πo) nowadays (Taylor, 1993; Bernanke et al., 1999; Woodford, 2003). The i is taken to be the anchor for a low and stable rate of inflation in an open economy model. Yet, some analysts, orthodox and heterodox alike, have challenged this belief arguing that CBs turn to the exchange rate (e) channel and adopt it as a second policy tool with the aim of meeting πo (Svensson, 1999; Hüfner, 2004). The purpose of this paper is to show that the veritable anchor of inflation is neither i nor e, but the wage rate and the unit labour costs (ULC). We conduct econometric analyses based on data from a set of inflation targeting countries. The main empirical findings support our hypothesis regarding the higher importance of wages and the ULC vis-à-vis i and e in the determination of the CPI.